Dose-response between frequency of breaks in sedentary time and glucose control in type 2 diabetes: A proof of concept study. Issue 7 (July 2019) - Paing, Aye C.; McMillan, Kathryn A.; Kirk, Alison F.; Collier, Andrew; Hewitt, Allan; Chastin, Sebastien F.M.
Abstract: Objectives: This study aimed to investigate dose-response between frequency of breaks in sedentary time and glucose control. Design: Randomised three-treatment, two-period balanced incomplete block trial. Methods: Twelve adults with type 2 diabetes (age, 60 ± 11 years; body mass index, 30.2 ± 4.7 kg/m 2 ) participated in two of the following treatment conditions: sitting for 7 h interrupted by 3 min light-intensity walking breaks every (1) 60 min (Condition 1), (2) 30 min (Condition 2), and (3) 15 min (Condition 3). Postprandial glucose incremental area under the curves (iAUCs) and 21-h glucose total area under the curve (AUC) were measured using continuous glucose monitoring. Standardised meals were provided. Results: Compared with Condition 1 (6.7 ± 0.8 mmol L −1 × 3.5 h −1 ), post-breakfast glucose iAUC was reduced for Condition 3 (3.5 ± 0.9 mmol L −1 × 3.5 h −1, p ˂ 0.04). Post-lunch glucose iAUC was lower in Condition 3 (1.3 ± 0.9 mmol L −1 × 3.5 h −1, p ˂ 0.03) and Condition 2 (2.1 ± 0.7 mmol L −1 × 3.5 h −1, p ˂ 0.05) relative to Condition 1 (4.6 ± 0.8 mmol L −1 × 3.5 h −1 ). Condition 3 (1.0 ± 0.7 mmol L −1 × 3.5 h −1, p = 0.02) and Condition 2 (1.6 ± 0.6 mmol L −1 × 3.5 h −1, p ˂ 0.04) attenuated post-dinner glucose iAUC compared with Condition 1 (4.0 ± 0.7 mmol L −1 × 3.5 h −1 ). Cumulative 10.5-h postprandial glucose iAUC was lower in Condition 3 than Condition 1 (p = 0.02). Condition 3 reduced 21-h glucose AUC compared with Condition 1 (p < 0.001) and Condition 2 (p = 0.002). However, post-breakfast glucose iAUC, cumulative 10.5-h postprandial glucose iAUC and 21-h glucose AUC were not different between Condition 2 and Condition 1 (p ˃ 0.05). Conclusions: There could be dose-response between frequency of breaks in sedentary time and glucose. Interrupting sedentary time every 15 min could produce better glucose control.